Computers and CTGs: where are we at? - Barber VS; Lean KA; Shakeshaft CE (British Journal of Midwifery, 2010)
The latest National Institute for Health and Clinical Excellence guidelines on intrapartum care include advice on the appropriate use of cardiotocographs. This technology has become, rightly or wrongly, commonplace as an increasing number of women are receiving CTG monitoring during their labour. The technology is now over 50 years old, however, it has still to be proven effective. The cardiotocograph monitors are not monitors per se--they are used as a recorder and signal display to be then reviewed by an observer. Increasingly computers have been used to improve this technology, both display and interpretation and computers are now to be used to help interpret traces in real time. This article addresses whether the potential in CTG monitoring technology has finally materialized.